Identification of hotspots for NO and N2O production and consumption in counter- and co-diffusion biofilms for simultaneous nitrification and denitrification. (December 2017) - Kinh, Co Thi; Riya, Shohei; Hosomi, Masaaki; Terada, Akihiko
Graphical abstract: Highlights: Trends in NO and N2 O production and consumption in an MABR and CBR were compared. The MABR achieved a 21% higher nitrogen removal rate than the CBR. MABR emits less NO and N2 O than CBR by factors of 2 and 28, respectively. The NO and N2 O production hotspots are closely located in the MABR aerobic region. Mechanisms of NO/N2 O production/consumption in an MABR and CBR are discussed. Abstract: A membrane-aerated biofilm reactor (MABR) provides a counter-current substrate diffusion geometry in which oxygen is supplied from a gas-permeable membrane on which a biofilm is grown. This study hypothesized that an MABR would mitigate NO and N2 O emissions compared with those from a conventional biofilm reactor (CBR). Two laboratory-scale reactors, representing an MABR and CBR, were operated by feeding synthetic industrial wastewater. The surficial nitrogen removal rate for the MABR [4.51 ± 0.52 g-N/(m 2 day)] was higher than that for the CBR [3.56 ± 0.81 g-N/(m 2 day)] ( p < 0.05). The abundance of β-proteobacterial ammonia-oxidizing bacteria in the MABR biofilm aerobic zone was high. The NO and N2 O concentrations at the biofilm–liquid interface in the MABR were 0.0066 ± 0.0014 and 0.01 ± 0.0009 mg-N/L, respectively, two and 28 times lower than those in the CBR. The NO and N2 O production hotspots were closely located in the MABR aerobic zone.